2003
DOI: 10.1027//0269-8803.17.3.113
|View full text |Cite
|
Sign up to set email alerts
|

Faster Choice-Reaction Times to Positive than to Negative Facial Expressions

Abstract: Several studies have shown faster choice-reaction times to positive than to negative facial expressions. The present study examined whether this effect is exclusively due to faster cognitive processing of positive stimuli (i.e., processes leading up to, and including, response selection), or whether it also involves faster motor execution of the selected response. In two experiments, response selection (onset of the lateralized readiness potential, LRP) and response execution (LRP onset-response onset) times f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
85
2
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 53 publications
16
85
2
3
Order By: Relevance
“…While, the findings from this research highlight the importance of the additional information provided by movement (i.e., movements of the facial features and the timing of these muscular movements) for the recognition of subtle facial expressions of emotion, the results can also be seen to complement existing work with static stimuli, such as better accuracy for the recognition of faces expressing the emotion of happiness. Recent choice-reaction work has suggested that choice responses towards pleasant faces are facilitated compared to unpleasant faces (Leppänen & Hietanen, 2004;Leppänen, Tenhunen, & Hietanen, 2003), so this raises the question of whether similar effects may have influenced the present findings. It therefore seems important that research begins to consider the recognition process in relation to dynamic as well as static stimuli portraying subtle expressions of emotion.…”
Section: Discussionmentioning
confidence: 49%
“…While, the findings from this research highlight the importance of the additional information provided by movement (i.e., movements of the facial features and the timing of these muscular movements) for the recognition of subtle facial expressions of emotion, the results can also be seen to complement existing work with static stimuli, such as better accuracy for the recognition of faces expressing the emotion of happiness. Recent choice-reaction work has suggested that choice responses towards pleasant faces are facilitated compared to unpleasant faces (Leppänen & Hietanen, 2004;Leppänen, Tenhunen, & Hietanen, 2003), so this raises the question of whether similar effects may have influenced the present findings. It therefore seems important that research begins to consider the recognition process in relation to dynamic as well as static stimuli portraying subtle expressions of emotion.…”
Section: Discussionmentioning
confidence: 49%
“…One possible explanation for these contradictory findings might be that the stimulus-response mappings were not entirely balanced in Leppänen and Hietanen's study [31] and the responses to neutral faces were always with the middle button. In addition, significant positive advantage effects (comparisons between positive faces and negative faces) were also observed, such that happy faces were classified faster than sad faces, which might relate to the superior cognitive encoding of positive expressions rather than negative expressions [31,32]. Moreover, face inversion effects were discovered for emotional faces but not for neutral faces, and participants had higher accuracy and faster response speeds when they Fig.…”
Section: Discussionmentioning
confidence: 76%
“…Recently, Leppänen, Tenhunen, and Hietanen (2003; see also argued that the typically observed HFA is actually an artifact of the experimental context. Because most experimental contexts are actually slightly hedonically positive, they argue that the match between the pleasant evaluative context of the experimental setting and the pleasant expression on a target's face leads to the HFA.…”
Section: The Happy Face Response Latency Advantagementioning
confidence: 97%